The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.7589/2013-03-063
|View full text |Cite
|
Sign up to set email alerts
|

Blood Mineral Concentrations in the Endangered Huemul Deer (Hippocamelus bisulcus) from Chilean Patagonia

Abstract: ABSTRACT:Concentrations of calcium, magnesium, copper, zinc, and selenium were measured in plasma from 11 huemul (Hippocamelus bisulcus) from Chilean Patagonia. Except for zinc and copper, concentrations of these minerals were similar to those of other deer species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
11
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 15 publications
2
11
0
1
Order By: Relevance
“…This pattern resembles that for white-tailed deer (McDowell et al 1995;Flueck et al 2012). The data reported by Chihuailaf et al (2014) suggest that most huemul were Se deficient by North American cattle standards. The role of Se deficiency thus merits further consideration in explaining huemul declines and in conservation efforts, especially given that soils in huemul habitat are Se deficient (Flueck et al 2014).…”
supporting
confidence: 59%
See 4 more Smart Citations
“…This pattern resembles that for white-tailed deer (McDowell et al 1995;Flueck et al 2012). The data reported by Chihuailaf et al (2014) suggest that most huemul were Se deficient by North American cattle standards. The role of Se deficiency thus merits further consideration in explaining huemul declines and in conservation efforts, especially given that soils in huemul habitat are Se deficient (Flueck et al 2014).…”
supporting
confidence: 59%
“…To help inform recovery efforts, Chihuailaf et al (2014) reported plasma mineral concentrations in endangered huemul deer (Hippocamelus bisulcus). They described plasma selenium (Se) concentrations as similar to those of other cervids and within reference intervals for white-tailed deer (Odocoileus virginianus), citing McDowell et al (1995).…”
mentioning
confidence: 99%
See 3 more Smart Citations